“CORPORATE SOCIAL RESPONSIBILITY IN THE REALM OF STAKEHOLDER POTENTIAL” - Dasgupta, Dr. Pooja; Dubey, Ms. Khushbu (IJRDO - Journal of Business Management, 2017)
The article discusses about the stakeholder theories that are prevalent in the industry and provides further insights on how stakeholder rights should be realized. The authors compare two forms of notions regarding the stakeholder theories and try to find out which one is more appropriate and how the same can be implemented. The authors try to find an alternative stakeholder policy which is firmer than the stakeholder theories which are currently put in place.